Pore water and solid-phase depth profiles of manganese and alkalinity from sediments taken during PELAGIA expedition 64PE401 to the northwestern Black Sea in 2015 - Lenstra, Wytze K; Slomp, Caroline P (PANGAEA, 2020)
Porewater depth profiles of dissolved manganese and alkalinity from cores that were sliced and subsamples under a nitrogen atmosphere. Total Mn sediment concentrations from cores that were sliced under a nitrogen atmosphere. Total Mn determined by HF dissolution and ICP-OES.
Keywords: Alkalinity; manganese; porewater